Homens autores de violência contra mulheres: um estudo com participantes de grupos reflexivos em Belo Horizonte - Fleury-Teixeira, Elizabeth Maria (Universidade Federal de São Carlos, 2021)
During 2019, in Belo Horizonte (MG), a total of 456 men who committed violence, punished by the Law 11.340 (Maria da Penha Law), were referred by the justice system to serve part of their alternative sentence in existing reflection groups in two programs in the city: Albam Institute and Dialogar Program of Civil Police of Minas Gerais State. There were respondents found by this survey. The data obtained resulted from the application of questionnaires to 30% of the total number of participants in these reflection groups operating in Belo Horizonte that year - meaning the application of 137 questionnaires related to childhood and 137 questionnaires on youth. The main purpose of this research was to carry out an empirical study in Belo Horizonte that would allow to find patterns related to practices based on beliefs and customs, moral values in which men who committed violence against women in intimate relationships were socialized, punished by the Maria da Penha Law. The way to make this proposal viable was to reconstruct the memories of primary and secondary socialization of these men, in view of an approximation with the dimension of the habitus (conf. Bourdieu 1979:164; e Bourdieu, 1980:88 e 89; Bourdieu, 1987:81structured in this trajectory. The tested hypothesis was built from the objective of exploring a little more the notion of an increase in violence associated with a movement to change the patterns of masculinity, in view of the notions brought by Connell and Messersmith (1985 and 2013); Walby (1991), Patman (1998), Bourdieu (1998) and Segato (2006).
Men authors of violence against women: a study with participants of reflective groups in Belo Horizonte
Keywords: Volência nas relações íntimas; Homens autores de violência; Socialização primária; Socialização secundária; Violence in intimate relationships; Male perpetrators of violence; Primary socialization; Secondary socialization; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS